Meningkatkan penerapan SAK EMKM dengan persepsi usaha dan kesiapan pelaku UMKM - Purnomo, Asri; Adyaksana, Rahandhika (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2021)
UMKM (Micro Small Medium Enterprises) plays an important role in developed countries, particularly in Indonesia, which works absorbing many workers to reduce the number of unemployment. This research aims to examine the effect on the application of accounting recording systems, accounting comprehensions, business perceptions, and UMKM preparedness in implementing SAK EMKM. The objects of the research are UMKM in Yogyakarta. The respondents were 120 UMKM owners. This study is using multiple regression analysis to examine the hypothesis. The research method uses purposive sampling under the criteria in UU No. 20 Tahun 2008 tentang Kriteria UMKM. The result indicates that the hypothesis of the accounting recording system and comprehensions does not affect the implementation of SAK EMKM. Meanwhile, the hypothesis of business perceptions and UMKM preparedness has significant positive effect on the implementation of SAK EMKM.